Development of a framework for the assessment of energy demand-based greenhouse gas mitigation options for the agriculture sector - Bonyad, Marziyeh; Shafique, Hafiz Umar; Mondal, Md. Hossain Alam; Subramanyam, Veena; Kumar, Amit; Ahiduzzaman, Md. (American Society of Agricultural and Biological Engineers, 2018)
Abstract. This study assesses greenhouse gas (GHG) mitigation options for the agriculture sector. The Long-range Energy Alternatives Planning (LEAP) model was used to develop a framework to assess future trends in energy demand and associated GHG emissions for the agriculture sector and to assess various GHG mitigation options associated with energy consumption. A business-as-usual (reference) scenario and 32 GHG mitigation scenarios were developed for the years 2009-2050 using the LEAP model. A case study for Alberta, Canada, was conducted. In the model, GHG mitigation scenarios were developed for the energy demand side (e.g., farm machines, farm transportation, lighting, and ventilation) based on efficiency improvements and the use of renewable energy. The mitigation scenarios were divided into two planning horizons based on technology penetration: slow penetration (2009-2050) and fast penetration (2009-2030). For each planning horizon, 16 scenarios were assessed. Of all farm machines, efficient diesel tractors have the highest GHG mitigation potential: 12.35 MT of CO2 equivalent by 2050 and 4.7 MT of CO2 equivalent by 2030. In addition, GHG abatement cost curves show that biodiesel tractors and efficient diesel tractors have the highest GHG mitigation potential, with attractive abatement costs of -$62 and -$11 tonne-1 of CO2 mitigated by 2050, respectively. Keywords: Abatement cost, Agriculture sector, Energy efficiency, GHG mitigation, LEAP model.